2023
DOI: 10.1097/ijg.0000000000002192
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Gonioscopy-Assisted Transluminal Trabeculotomy for Primary Congenital Glaucoma

Abstract: Précis: Gonioscopy-assisted transluminal trabeculotomy (GATT) provided effective intraocular pressure (IOP) control in primary congenital glaucoma (PCG). Also, approximately two third of patients did not need antiglaucoma medication at an average follow-up of 1 year after surgery.Purpose: The purpose of this study was to assess the safety and efficacy of GATT surgery in eyes with PCG. Materials and Methods:This study is a retrospective review of patients who underwent GATT surgery for PCG. Outcome measures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 19 publications
(50 reference statements)
2
7
0
Order By: Relevance
“…Additionally, our GATT study demonstrated excellent complete and partial success rates, consistent with previous reports [6,7,16,17].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Additionally, our GATT study demonstrated excellent complete and partial success rates, consistent with previous reports [6,7,16,17].…”
Section: Discussionsupporting
confidence: 91%
“…It is reasonable speculation that a larger incision angle equates to more open areas for aqueous ow, thereby achieving a more optimal IOP-lowering effect. Nevertheless, there are still con icting views on the relationship between incision angle and surgical success rate, as well as its possible mechanisms [7,21,25]. In this study, we attempted a 360° trabeculotomy in each case.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Chira-Adisai et al observed a decrease in mean IOP from 21.8 ± 5.4 mm Hg to 14.5 ± 0.8 mm Hg at the 1-year follow-up, with a success rate of 71.8% at the last follow-up 79 . GATT has also been described as an effective approach for the management of uveitic glaucoma, steroid-induced glaucoma (IOP reduction up to 63%), PXG, juvenile OAG, and primary congenital glaucoma 80–85 …”
Section: Non-bleb Forming Trabecular Meshwork Canal Cleaving Approachesmentioning
confidence: 99%
“…79 GATT has also been described as an effective approach for the management of uveitic glaucoma, steroid-induced glaucoma (IOP reduction up to 63%), PXG, juvenile OAG, and primary congenital glaucoma. [80][81][82][83][84][85] Several studies have demonstrated the strong efficacy of GATT compared with other MIGS. Yalinbas et al compared ab externo trabeculotomy with ab interno trabeculotomy and reported similar IOP reduction at 12 months in both groups.…”
Section: Gonioscopy-assisted Transluminal Trabeculotomymentioning
confidence: 99%